Cote d'Ivoire Economic Update, March 2015 : Ivorian Economic Performance since the End of the Post-Election Crisis - World Bank Group (World Bank, Abidjan, 2015)
First in a series, which aims to analyze the recent economic and financial situation in Côte d'Ivoire, this report analyzes the main macroeconomic developments and structural policies of the country from 2013 until mid-2014. It also reflects on the underlying factors of the strong economic recovery in Côte d'Ivoire since the end of the post-election crisis, to assess the likelihood of sustained economic growth and significant poverty reduction in the country. Finally, the report analyzes the effects of declining oil prices and the appreciation of the dollar against the euro and the CFA franc on the Ivorian economy. This edition does not examine the impact of strong economic growth on the Ivoirian population's well-being indicators such as, poverty, employment and inequality. Within the scope of this report, the objective is to understand the factors contributing to the strong economic recovery in Côte d'Ivoire. This economic update is targeted toward a larger audience, in order to stimulate constructive debate on public policy in the country and between the country and its development partners.